CHANGES IN THE TEETH ROWS STRUCTURE OF THE TADPOLES OF POLYPEDATES LEUCOMYSTAX WITH REFERENCE TO FOOD AND FEEDING HABITS - IANGRAI, ASORPHI; HOOROO, R.N.K.; GUPTA, B.B.P.; CHATTERJEE, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
One important characteristic feature of anuran tadpoles is the development of their mouth. Development of mouth began soon after hatching. In the present study we observed that Polypedates leucomystax tadpoles are pond dwellers and there is ontogenetic variation in the labial teeth rows. Complete labial teeth row was observed in stage 31 to 39 and the dental formula was 1 : 3+3/3. Tadpoles start feeding from stage 25 and food item comprises mainly of phytoplankton and zooplankton. At stage 40 the tadpoles stop feeding and at stage 46 metamorphosis was completed and the froglet start feeding on a carnivorous diet.